Effect of concrete waste particles on infiltration characteristics of soil - Rahardjo, Harianto (2019)
Demolition of old buildings to create space for new development resulted in the near surface soil (topsoil) to be mixed with particles derived mostly from concrete wastes. This condition could affect the infiltration capacity and surface runoff, therefore, storm-water management of the area. This paper presents results of study on the effect of concrete waste particles on the hydraulic properties and infiltration capacity of the topsoil. Laboratory tests were performed to compare the hydraulic properties of the topsoil and the mixture of topsoil and concrete particles. Laboratory infiltration column test was performed on the mixture to evaluate its infiltration capacity. Results from the laboratory tests indicated that the presence of particles from concrete waste decreased the water-holding capacity and permeability, thereby the infiltration capacity of the ground surface. The results were supported by numerical analysis performed using the same material and boundary conditions as the column test. Parametric study was performed on both the topsoil and the mixture to extend the results of infiltration test to different materials under different ranges of rainfall intensity. The parametric study showed that the presence of concrete particles increased the run-off and the effect increased as the rainfall intensity increased. Therefore, the increase in runoff coefficient should be considered for the storm-water management when the near surface soil is mixed with concrete waste.